Cover Image, Volume 185A, Number 9, September 2021. Issue 9 (16th August 2021) - Unknown
Abstract : Cover Image John M Graham, Jr, MD, ScD, teacher, mentor, scholar and master clinician, enjoying the moment by Moraine Lake during the 39th annual David W. Smith Workshop (2018) in Banff, Alberta, Canada.